Penerapan Terapi Storytelling pada Anak yang Mengalami Hospitalisasi dengan Demam Berdarah Dengue - Karimah, Farradina Vidya; Purnamawati, IGA Dewi (Neolectura, 2026)
Children who are hospitalized due to illness often experience anxiety due to separation from their parents, a new environment, and physical discomfort due to illness. Therefore, an intervention is needed to reduce children's anxiety so that they can receive treatment cooperatively. Storytelling therapy can be a solution for children who are hospitalized because it can reduce anxiety in children. The application of storytelling therapy in this study was given to children with dengue fever who experienced anxiety due to hospitalization. To reduce the anxiety of children hospitalized with dengue fever. A nursing care case study and the application of storytelling in children hospitalized with dengue fever. The application was carried out on a 14-year-old boy with dengue fever. The application of storytelling for 5 to 10 minutes with a frequency of 2x/day for three days was proven to be able to reduce the child's anxiety level. The final evaluation results showed a decrease in the anxiety level from 8 to 3 on the third day. Storytelling therapy can be applied to reduce anxiety through a nursing process approach via nursing care for children with dengue hemorrhagic fever.